Emerging Role of Adipocyte Dysfunction in Inducing Heart Failure Among Obese Patients With Prediabetes and Known Diabetes Mellitus - Berezin, Alexander E.; Berezin, Alexander A.; Lichtenauer, Michael (Frontiers in Cardiovascular Medicine, 2020)
Adipose tissue dysfunction is a predictor for cardiovascular (CV) events and heart failure (HF) in patient population with obesity, metabolic syndrome and known type 2 diabetes mellitus. Previous pre-clinical and clinical studies have yielded controversial findings regarding the role of accumulation of adipose tissue various types in CV risk and HF-related clinical outcomes in obese patients. There is evidence for direct impact of infiltration of epicardial adipocytes into the underlying myocardium to induce adverse cardiac remodeling and mediate HF development and atrial fibrillation. Additionally, perivascular adipocytes accumulation is responsible for release of pro-inflammatory adipocytokines (adiponectin, leptin, resistin), stimulation of oxidative stress, macrophage phenotype switching, worsening vascular reparation, that all lead to microvascular inflammation, endothelial dysfunction, atherosclerosis acceleration and finally to increase in CV mortality. However, systemic effects of white and brown adipose tissue can be different and adipogenesis including browning of adipose tissue and deficiency of anti-inflammatory adipocytokines (visfatin, omentin, Zinc-α2-glycoprotein, glypican-4) was frequently associated with adipose triglyceride lipase augmentation, altered glucose homeostasis, resistance to insulin of skeletal muscles, increased cardiomyocyte apoptosis, lowered survival and weak function of progenitor endothelial cells, which could significantly influence on HF development, as well as end-organ fibrosis, and multiple comorbidities. The exact underlying mechanisms for these effects are not fully understood, while they are essential to help develop improved treatment strategies. The aim of the review is to summarize the evidence showing that adipocyte dysfunction may induce the onset of HF and support advance of HF through different biological mechanisms involving inflammation, pericardial and perivascular adipose tissue accumulation, adverse and electrical cardiac remodeling, and skeletal muscle dysfunction. The unbalancing effects of natriuretic peptides, neprilysin, components of renin-angiotensin system, as exacerbating cause of altered adipocytokine signaling on myocardium and vasculature amid obesity patients at high risk of HF is disputed. The profile of pro- and anti-inflammatory adipocytokines as promising biomarker for HF risk stratification is discussed in the review.